Turn-Taking Strategies in Talk Show Interviews: A Qualitative Study of K-Pop Idol BTS on The Tonight Show - Purwanti, Eko; Cahyani, Ananda Pramesti Regita; Meisa, Wistri; Suryadi, Dedi; Sari, Mariska Intan; Pasandalan, Sittie Noffaisah (Universitas Ahmad Dahlan, 2025)
Turn-taking plays a vital role in managing and structuring conversations, making it especially important in both everyday interactions and educational environments. While much research has explored turn-taking in classroom or casual settings, limited attention has been given to how it operates in bilingual or multilingual media interviews. This study seeks to fill that gap by examining the turn-taking strategies used during interviews between Jimmy Fallon and K-Pop Idol BTS (Bangtan Sonyeondan), a globally recognized Korean boy band, on The Tonight Show Starring Jimmy Fallon. Employing a qualitative method, the study analyzed three interview videos through transcription and manual coding, guided by Stenstrom’s framework of turn-taking strategies. The analysis identified three main strategies: Taking the Turn (TTS), Holding the Turn (HTS), and Yielding the Turn (YTS). Among these, Taking the Turn (TTS) emerged as the most dominant, appearing in 47% of instances—emphasizing its key role in shaping the dynamic flow of K-Pop Idol interviews. These findings offer valuable insights for language learners and educators by demonstrating authentic conversational strategies in multilingual contexts. Furthermore, these findings may also serve as practical references for media professionals and interviewers aiming to manage turn-taking more effectively during live interactions.